The k-means clustering technique: General considerations and implementation in Mathematica - Morissette, Laurence; Chartier, Sylvain (Tutorials in quantitative methods for psychology, 2013)
Data clustering techniques are valuable tools for researchers working with large databases of multivariate data. In this tutorial, we present a simple yet powerful one: the k-means clustering technique, through three different algorithms: the Forgy/Lloyd, algorithm, the MacQueen algorithm and the Hartigan and Wong algorithm. We then present an implementation in Mathematica and various examples of the different options available to illustrate the application of the technique.